The Hedonic Econometric Model and Sourcing Management of the Cadastral Value of Land - Nailya Malikovna Yakupova; Ekaterina Ivanovna Kadochnikova; Venera Ildarovna Fakhrutdinova; Igor Leonidovich Beilin (International Journal of Supply Chain Management, 2019)
The authors identified and evaluated the key hedonic factors of cadastral value of land for individual housing construction. In order to identify the observed factors determining the value of land plots, linear, power and exponential specifications of the regression hedonic model of cadastral value based on data on 160 land plots in the city were constructed based on the source management. Zelenodolsk in 2019. The empirical estimates of the specifications presented in the article confirmed the hypothesis about the influence of the distance to the region capital of the Russian Federation, the distance to the railway, the distance to the nearest recreational zone, the distance to the nearest water body, the land area on its cadastral value. The greatest impact on the cadastral value of land plots is the distance to the capital of the Russian Federation and the land area. The influence of the coefficient of the length of the land plot on its cadastral value in all built specifications was not confirmed. The quality of the results was tested using Fisher test, student test, regression equation specification error test (RESET), testing of regression residues on heteroskedasticity and autocorrelation (White test, Breusch-Pagan test). The results of the empirical estimates confirmed the feasibility of the practical use of this approach to the assessment of the cadastral value of land.